Status of canine vaccination and the prevalence of rabies in humans and dogs in Plateau State, Nigeria 1998-2007 - McCrindle, Cheryl Myra Ethelwyn (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2009.